Transliteration or Transcription: Case for Indic Language Use in British Public Libraries - Rait, S. K. (Journal of Information and Knowledge, 1981)
Discusses the need for a scheme of script conversion of Indic languages for use in the British Public Libraries. Discusses the amendments to the Library of Congress’s scheme for script conversion. Use of the diacritical marks and the local variations to he adopted for different Indie languages have been emphasised.